Early prediction of reading comprehension within the simple view framework - Catts, Hugh W.; Herrera, Sarah; Nielsen, Diane Corcoran; Bridges, Mindy Sittner (Reading & writing, 2015)
The simple view of reading proposes that reading comprehension is the product of word reading and language comprehension. In this study, we used the simple view framework to examine the early prediction of reading comprehension abilities. Using multiple measures for all constructs, we assessed word reading precursors (i.e., letter knowledge, phonological awareness, rapid naming) and oral language at the beginning of kindergarten and reading comprehension at the end of third grade. Word reading was also assessed at the end of second grade and served as a mediator. Structural equation modeling showed that precursors of word reading and language comprehension accurately predicted reading comprehension in both mediated and non-mediated models. The results have important implications for the early identification of reading comprehension difficulties.